The Impact of Corporate Social Responsibility on Sustainable Financial Performance: The Mediating Role of Brand Value in Nepalese Commercial Banks - Subedi, Dhruba Prasad; Bhandari, Dilli Ram (Journal of Nepalese Business Studies, 2024)
Corporate social responsibility lies in its ability to strengthen brand value, leading to increased customer trust, competitive advantage, and sustainable financial performance over time. Corporate social responsibility strengthens brand value by demonstrating a company's commitment to ethical practices, social welfare, and environmental sustainability, which enhances its reputation and customer loyalty. This study aims to investigate how brand value impacts the relationship between corporate social responsibility and sustainable financial performance in Nepalese commercial banks. To accomplish this objective, data were collected from 252 respondents using a structured questionnaire, which was distributed via a convenience sampling method. The participants consisted of employees at managerial and officer level employees from various commercial banks. Data analysis was conducted using Process Macro 4, applying a 95% confidence interval and 5,000 bootstrapping samples. The findings reveal that brand value serves as a complete mediator in the relationship between corporate social responsibility and sustainable financial performance. This study demonstrates that organizations that are investing in corporate social responsibility play a pivotal role in enhancing brand value by demonstrating the organizational commitment to social and environmental well-being. Implementing corporate social responsibility initiatives can enhance sustainable financial performance by strengthening brand value, which fosters customer trust and loyalty, ultimately supporting long-term profitability and resilience.